Employee meaning and wellbeing : the responsible organisation - Zicari, Adrián; Gamble, Tom (Routledge CoBS focus on responsible business., 2025)
"The Covid-19 pandemic sparked a latent desire for a more balanced, more meaningful and freer approach to work for millions of employees throughout the world. Growing interest in responsible business, in addition to the influence of the UN SDGs and inclusive growth, have also in many ways shifted the balance of power - or at least choice - to the employee. Sensitive to work-life balance, aware of the effects of overwork and short-term profit seeking, seeking meaning in their companies and jobs, employee demands have placed a huge strain on corporations caught between keeping to traditional ways of control and performance objectives though aware of the need to retain talent and create flexible solutions in order to reach their financial and production goals. In this book, leading academics, researchers and practitioners in the field of CSR, management, leadership and human resources from the 12 schools and corporate partners of the Council on Business & Society offer their latest cutting-edge research to explore how both employees and their organisations can reach win-win agreement in the working relationship. Meaning and mission are covered, as well as spirituality and purpose. Negative workplace practices leading to employee mental and physical illness are explored and ways to avoid these, with several positive approaches to employee commitment and wellbeing offered. Each insight is accompanied by key takeaways and food for thought sections, with each chapter featuring a micro-case study. Drawing on high-level research and transformed into engaging and accessible content, this book is written for students and scholars wishing to deepen their knowledge of the employee-leadership-workplace environment dimension, instructors seeking insight and learning content, and for professionals aiming to deepen their understanding of managing in the post-pandemic era"--